Biological structures scanning in design of tactile instructional material for visually impaired people - Alves Junior, Mauro Inácio; Ambrósio, Lívia Cristina; Mota, Lígia Souza Lima Silveira da; Medola, Fausto Orsi; Paschoarelli, Luis Carlos (DAT Journal, 2023)
Assistive Design is characterized by the development of Assistive Technologies, which promote functionality and inclusion of people with disabilities. The development of instructional material for teaching people with visual impairment can occur through the new technologies of 3D scanning and printing. This study aimed to develop tactile instructional material, based on snake biological structures. Skulls, heads, scales and tails of different species were scanned. The digital files were edited in specific software. Procedures of verification and analysis of the factors and parameters that imply in a better definition and accuracy of the virtual models were described, controlling the dimensional relation with the perception of details such as scales and anatomical format. The prototypes were obtained by 3D printing technology, allowing the analysis of factors and parameters that implied in a better accuracy of the details; besides the possibility of validation of the use interaction (effectiveness and efficiency) in educational conditions.